Evaluating the Effectiveness of Arbitration as ADR Mechanism in Commercial Disputes - Sarwa Kubira Nakayiza (Uganda Christian University, 2025)
This study evaluates the logicality of Alternative Dispute Resolution in facilitating the tenacity of commercial disputes in Uganda. The inspection was done through different case-studies as a diagnostic technique involving theoretical analysis of functioning literature, legislation and the cases adjudged by the courts in Uganda. With the aim of demonstrating how the Ugandan judiciary has assisted the growth of the process. This study observes that the courts in Uganda are naturally corroborative deploying the alternative dispute resolution mechanisms as explained by the liability to recognise a valid arbitration convention and unwillingness to examine evidence that is before an arbitral tribunal among others. It also considers some barriers that need to be addressed involving: a deep-seated trust deficit; the lack of an ‘Africa focused’ alternative dispute resolution practices; the lack of diversity, knowledge gaps among lawyers on how Alternative Dispute Resolution mechanisms operate and many others. The research discusses the challenges and problems while providing recommendations for the different key players in Uganda to scan regular steps in icing a prosperous domestic and international Alternative Dispute Resolution